2005
DOI: 10.1111/j.1399-3011.2005.00304.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of aromatic side chain size complementarity in the hydrophobic core of a designed coiled‐coil

Abstract: The coiled-coil structure plays an important roles, especially in protein assembly. Previously we constructed AAB-type heterotrimeric coiled-coils by manipulating the packing in the hydrophobic core using Trp and Ala residues, where one Trp and two Ala residues were placed in the hydrophobic core instead of three Ile residues. To optimize the packing complementarity in the hydrophobic core, we investigated the effects of introducing various aromatic amino acids on the formation of an AAB-type heterotrimeric co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Moreover, substitution of a single hydrophobic position with tyrosine (L 15 Y) in the Y a L d E e E g mutant results in a significant reduction in the spot intensity compared to that of wt Acid-pp. As already discussed, despite the similarity in size between Phe and Tyr residues, they exhibit prominent differences in the coiled-coil formation that are probably due to the destabilizing orientation of the polar hydroxyl group towards the hydrophobic core [21]. The clear decrease in binding affinity between chimera and Tyr-comprising mutants shows that the side chains at the artificial interface of the helix bundle experience an environment similar to that of natural coiled coils.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, substitution of a single hydrophobic position with tyrosine (L 15 Y) in the Y a L d E e E g mutant results in a significant reduction in the spot intensity compared to that of wt Acid-pp. As already discussed, despite the similarity in size between Phe and Tyr residues, they exhibit prominent differences in the coiled-coil formation that are probably due to the destabilizing orientation of the polar hydroxyl group towards the hydrophobic core [21]. The clear decrease in binding affinity between chimera and Tyr-comprising mutants shows that the side chains at the artificial interface of the helix bundle experience an environment similar to that of natural coiled coils.…”
Section: Resultsmentioning
confidence: 99%
“…The protein has the turn structures from the three linkers and the extra portions at the N‐ and C‐termini, and these parts comprise 18% of the total amino acids. Taking it into account, the protein is considered to form a coiled‐coil structure, although the ratio of [θ] 222 to [θ] 208 is less than 1 45. The AM2E protein also exhibited the same spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…Once again, this can be understood in terms of both protein folding and interactions between a protein and its molecular environment. Since the hydrophobic core of a protein is normally tightly packed, a significant change of amino acid residues' size within the core can disrupt the thermal stability and the correct folding of protein structure, an effect which has been shown in de novo design of proteins (e.g., Sakurai et al, 2005) and sitedirected mutagenesis (e.g., RNase A as reported in Kadonosono et al (2003), ubiquitin as reported in Benitez-Cardoza et al (2004)). Plentiful empirical evidence further links amino acid size to inter-molecular interactions.…”
Section: Article In Pressmentioning
confidence: 95%